(untitled) (Docentes 2.0 Journal, 2021)
The pandemic caused by SARS-CoV-2 has affected many aspects of human development, and especially the education of students of all ages, having to abruptly incorporate elements of virtual teaching in environments where they were not even considered. Assessment during the pandemic has been mostly developed online, evidencing the limited knowledge of the teaching community regarding online assessment methods. The need to know and use online assessment tools has arisen in the world of education. In response to this situation, a review of the online assessment and test proctoring tools available in the educational community, as well as an analysis of their limitations and alternatives to them, has been collected in this essay. In addition, a model, adapted to the age and characteristics of the learner, of online assessment systems has been proposed as a frame of reference addressed to the educational community responsible for the training of future promotions in these post-pandemic times.